CAUSES AND PREVENTION OF INFERTILITY IN WOMEN AND MODERN METHODS OF PREGNANCY MANAGEMENT - Saparbaeva N.R; Sadullaev O.K; Anvarova S.A (Scholar Express Journals, 2025)
This article examines the main causes of female infertility, including hormonal, anatomical, genetic, and immunological factors. It discusses diagnostic methods for reproductive disorders and modern treatment approaches such as medication and assisted reproductive technologies. Special attention is given to infertility prevention, including timely treatment of gynecological diseases and maintaining a healthy lifestyle. The second part of the article focuses on current methods of pregnancy management aimed at ensuring the health of both mother and fetus
Keywords: infertility; women’s health; reproductive system; prevention